Data‐driven–based attitude control of combined spacecraft with noncooperative target. (13th August 2019) - Jiang, Huaiyuan; Zhou, Bin; Li, Dongxu; Duan, Guangren
Summary: In this paper, the attitude control of combined spacecraft with noncooperative target is studied. For the linearized system of the attitude control system, which possesses uncertainties on both its control and system matrices caused by the noncooperative target, this paper proposes an approximated iteration method to obtain the optimal controller such that the closed‐loop system possesses a prescribed convergence rate. An explicit stabilizing gain is established to initiate the iteration method. Based on the proposed iteration method and the initial stabilizing gain, a data‐driven algorithm is proposed to obtain the optimal controller for the attitude control system without using the system parameter information. A simulation is given to verify the effectiveness of the proposed method.